2020
DOI: 10.1155/2020/3906129
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and Its Determinants among Male and Female Adolescents in Southern Ethiopia: A Comparative Cross-Sectional Study

Abstract: Background. Adolescent anemia is a major public health problem worldwide. Adolescents (10–19 years) are at an increased risk of developing anemia due to increased iron demand during puberty, menstrual losses, limited dietary iron intake, and faulty dietary habits. Objective. To assess the prevalence of anemia and associated factors among male and female adolescent students in Dilla Town, Gedeo Zone, Southern Ethiopia, May 2018. Methods. A school-based comparative cross-sectional study was employed among 742 sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
6
0
5
Order By: Relevance
“…Hence, much attention should be paid to the anemia problem in the plateau areas and appropriate interventions should be taken to prevent and treat anemia. The incidence of anemia in women is significantly higher than that in men, which may be related to factors such as hemorrhage in women's physiological period, pregnancy, lactation, and internal hormones 11 . In addition, compared with the eastern plain area, the medical strength of gynecology and obstetrics is weak, and the socioeconomic development and cultural cognition level are relatively low 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, much attention should be paid to the anemia problem in the plateau areas and appropriate interventions should be taken to prevent and treat anemia. The incidence of anemia in women is significantly higher than that in men, which may be related to factors such as hemorrhage in women's physiological period, pregnancy, lactation, and internal hormones 11 . In addition, compared with the eastern plain area, the medical strength of gynecology and obstetrics is weak, and the socioeconomic development and cultural cognition level are relatively low 12 .…”
Section: Discussionmentioning
confidence: 99%
“…This finding is inconsistent across studies. Research carried out in Ethiopia, for example, has found that anemia levels are lower in 10–13-year-old boys than older adolescents ( 59 ); however, other studies have demonstrated that anemia is higher among early adolescent years (10–13 years) compared with the late adolescent period ( 60 ). Another study in Nepal concluded that the anemia level in older boys and girls (15–19 years) is higher than the anemia level in younger children ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…45 Kebutuhan absorpsi zat besi memuncak pada usia 14-15 tahun pada remaja putri. 46 Pada penelitian yang dilakukan oleh Nelima et al (2015) menunjukkan bahwa remaja putri yang memiliki asupan zat besi rendah akan berisiko 9 kali lebih besar untuk menderita anemia dibandingkan remaja putri yang memiliki asupan zat besi yang cukup. 47 Anemia memiliki konsekuensi serius pada masa remaja dengan retardasi pertumbuhan serta gangguan fisik dan kinerja kognitif.…”
Section: Asupan Protein Dan Zat Besiunclassified